Functional role of endogenous Kv1.4 in experimental demyelination - Gonzalez Alvarado, Maria; Rötger, Caroline; Berger, Laura; London, Barry; Haase, Stefanie; Kuhbandner, Kristina; Lee, De Hyung; Linker, Ralf A. (Journal of Neuroimmunology, 2020)
During neuroinflammation, the shaker type potassium channel Kv1.4 is re-expressed in oligodendrocytes (Ol), but not immune cells. Here, we analyze the role of endogenous Kv1.4 in two demyelinating animal models of multiple sclerosis. While Kv1.4 deficiency in primary murine Ol led to a decreased proliferation rate in vitro, it did not exert an effect on Ol proliferation or on the extent of de- or remyelination in the cuprizone model in vivo. However, in experimental autoimmune encephalomyelitis, Kv1.4−/− mice exhibited a milder disease course and reduced Th1 responses. These data argue for an indirect effect of Kv1.4 on immune cells, possibly via glial cells.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Cuprizone; EAE; Kv1.4; Multiple sclerosis; Oligodendrocytes; Remyelination